Topical issues of urinary tract infection in infants - T.V. Budnik (Zaslavsky O.Yu., 2020)
The article presents contemporary views of foreign authors on the issues of the prevalence, etiology and pathogenesis, diagnosis, treatment and prevention of urinary tract infection (UTI) in young children (0-3 years). The point is that UTI remains the most common infection in children under 2 years and ranks second to third among all childhood infections. UTIs remain a global problem in pediatrics. Diagnosis of the disease is not a simple issue in children aged 0-3 years. Thus, the neonatal period is characterized by nonspecific symptoms and signs of UTI: temperature instability, peripheral circulation disorders, lethargy, irritability, apnea, anorexia, poor suction, vomiting, prolonged jaundice, etc. Urinary syndrome is rare in them, but is considered more specific. Newborns with UTI have a high risk of bacteremia, which indicates the relevance of the hematogenous pathway of infection spread. It is proved that children with functional or anatomic pathology of the urinary system, with immunodeficiency are prone to UTI. The importance of timely diagnosis of the disease and the risk of factors for its implementation are emphasized. In this sense, the development of non-invasive methods and devices for collecting urine from babies with the highest risk of sample contamination is of particular importance. There is an urgent need to identify more specific biomarkers to improve the accuracy and speed of diagnosis of UTI, a need in modern bacteriological methods of cultural identification. New non-invasive methods of testing are being tested, such as magnetic resonance imaging without contrast and ultrasound Doppler techniques for tissue and microvascular imaging. Some aspects of UTI remain controversial. These include issues of the natural development of the disease, optimal variants of antibacterial regimen, preventive management of the patient, etc. In recent years, worldwide resistance to antimicrobials has increased with the emergence of organisms that produce beta-lactamase with a broad spectrum. Therefore, the least broad-spectrum antibiotic should be used, and it is necessary to take into account local sensitivity data. Recurrent UTI usually does not lead to renal scarring in children without structural abnormality of the kidney. Thus, routine antimicrobial prophylaxis is rarely justified, given the side effects and emergence of resistance. In this sense, it is appropriate to develop new vaccine compositions and formulations for the treatment and prevention of recurrent UTI, in particular in young children.